Islamic Psychotherapy In Rehabilitation: A Multi-Site Study To Build The Spiritual Intelligence Of Former Drug Addicts - Suroyya, Naharin (Jurnal Penelitian, 2025)
Indonesia's "drug emergency" is a term that has emerged due to the increasingly widespread circulation and abuse of drugs in society. Data from the Indonesian National Narcotics Board (BNN) for 2024 shows drug abuse prevalence among ages 15-64 is 5.8%, and in 2023 it was 1.73%. This figure indicates an increase of 4.07%. This situation has influenced the rising number of former drug addicts undergoing rehabilitation at Al Ghozali Islamic Boarding School in Kediri and Sirajuth Tholibin Dua Saman Al Hadad Islamic Boarding School in Blitar. Both boarding schools use an Islamic psychotherapy approach as a means of rehabilitation to develop the spiritual intelligence of former drug addicts. The purpose of this research is to understand the process and post-rehabilitation changes resulting from the Islamic psychotherapy approach. The study uses a qualitative approach with a multi-site research design. The research findings are: (1) The rehabilitation process begins with identity registration, an assessment of individual needs, individual counseling spiritual guidance ("siraman rohani") provided by the caregivers, and rehabilitation support. (2) Post-rehabilitation changes include: awareness of the obligation to worship, application of the concepts of hablum minallah and hablum minannas, a tendency to forgive and be compassionate, caution in speech and action, and the courage to take responsibility. Thus, Islamic psychotherapy not only cures drug addiction but also helps build spiritual resilience in individuals.